Factors Influencing Community Resource Mobilization to Support Households in Achieving Sustainable Poverty Alleviation: The Case of Dao People in Thanh Hoa Province, Vietnam - Duyên Nguyen Thi; Thuy Thanh Dao (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2024)
This article explains the factors influencing community resource mobilization in achieving sustainable poverty alleviation focusing on Dao households in Vietnam. It found that two factors influenced community resource mobilization to help Dao households sustainably escape poverty focuses on two dimensions: internal and external factors. Internal factors include education level, occupation, skills, experience, the number of healthy workers in the household, and the household's physical capital resources. External factors encompass broader influences such as state policies and support from state organizations and non-governmental organizations. While internal factors are crucial in determining the ability to mobilize community resources, external factors, though not decisive, play a significant role in facilitating the mobilization of these resources to support the Dao people in Thanh Hoa in achieving sustainable poverty alleviation. This study contributes to the study on how poverty should be alleviated in communal levels in Asia with a special reference to Vietnam.